2016
DOI: 10.1016/j.trsl.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Innate inflammation in type 1 diabetes

Abstract: Type 1 diabetes mellitus (T1D) is an autoimmune disease often diagnosed in childhood that results in pancreatic β-cell destruction and life-long insulin dependence. T1D susceptibility involves a complex interplay of genetic and environmental factors and has historically been attributed to adaptive immunity, though there is now increasing evidence for a role of innate inflammation. Here, we review studies that define a heightened age-dependent innate inflammatory state in T1D families that is paralleled with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 131 publications
(149 reference statements)
3
63
0
1
Order By: Relevance
“…The unused single-end reads were combined with the unmapped reads and cd-hit-dup from the CD-HIT software suite 63 was used to remove duplicate reads. Velvet was then run over a range of k-mer sizes (27,31,35,39,43,47,51,55,59,63) with the IDBA-UD contigs as long read input (velveth parameters: -long contig.fa, velvetg parameter: -conserveLong yes). Afterwards, all newly assembled contig sequences from the different k-mer runs and the original IDBA-UD contigs were concatenated and clustered using cd-hit from the CD-HIT software suite (parameter: -c 0.99) to remove redundancy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unused single-end reads were combined with the unmapped reads and cd-hit-dup from the CD-HIT software suite 63 was used to remove duplicate reads. Velvet was then run over a range of k-mer sizes (27,31,35,39,43,47,51,55,59,63) with the IDBA-UD contigs as long read input (velveth parameters: -long contig.fa, velvetg parameter: -conserveLong yes). Afterwards, all newly assembled contig sequences from the different k-mer runs and the original IDBA-UD contigs were concatenated and clustered using cd-hit from the CD-HIT software suite (parameter: -c 0.99) to remove redundancy.…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about changes in the function of the gastrointestinal tract with respect to T1DM traits, such as the proposed heightened innate inflammatory state 27 . Among the ten human proteins with the greatest changes in abundance in the faeces of individuals with T1DM (Supplementary Table 5), we identified two with higher abundance in the individuals with T1DM, namely lactotransferrin (LTF) and the lactotransferrin receptor intelectin (ITLN1), which maintain an important functional position at the crossroads of iron uptake, innate immunity and insulin function [40][41][42][43] , and whose antimicrobial activity may influence the gastrointestinal microbiota 44 (Supplementary Section 18 and Supplementary Fig.…”
Section: Human Protein Excretion In T1dm and Microbial Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 diabetes is an inflammatory autoimmune disease, resulting in a lack of insulin (Cabrera et al 2016;Price and Tarbell 2015). It has been proposed that impairment of some tissues such as skeletal muscles and adipose tissue accrued following type 1 diabetes is associated with incorrect protein folding (Takada et al 2007;Ono et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical systemic inflammation and changes of a wide variety of inflammatory markers together with the alterations of the metabolic syndrome, including IR, have been found in DM [79,80]. Rathcke and Vestergaard [81] first reported that CHI3L1 levels increased significantly in T2DM patients.…”
Section: Chi3l1 and Diabetesmentioning
confidence: 99%